Dvorak's guide to PC telecommunications. - Dvorak, John C. (Berkeley, USA : McGraw-Hill, Inc., 1990)
"You'll find out all about modems, how they work and how to best use them; tips and tricks for linking two remote computers; and how to establish an office at home. You'll also learn about each of the major electronic mail systems and bulletin board services-what they are and how they can work for you. The authors review the most popular telecommunications packages, the on-line services, obscure databases everything you want to know about." (Copied from the paste).
Foreword. Acknowledgments. Preface. Other osborne/McGraw-Hill books of interest to you. Why this book is for you. Part one. Alayman's view. Part Two. A technical view. Part three. User guides. Part Four. Appendixes. Index.
Includes floppy disk.
Keywords: COMMUNICATIONS SOFTWARE; DATA PROCESSING; MICROCOMPUTERS; ON-LINE SYSTEMS; TELECOMMUNICATION; ELECTRONIC DATA PROCESSING; SOFTWARE DE TELECOMUNICACIONES; PROCESO DE DATOS; MICROCOMPUTADORES; SISTEMAS EN LÍNEA; TELECOMUNICACIONES; PROCESAMIENTO ELECTRÓNICO DE DATOS